Is your local government plugged in? Highlights of Electronic Government Survey 2000, conducted by the International City/County Management Association and Public Technology, Inc. - Norris, Donald; Fletcher, Patricia; Holden, Stephen (Public Management (00333611), 2001)
In fall 2000, the International City/County Management Association and Public Technology Inc. carried out a survey of city and county governments to examine their use of electronic government. The survey was mailed to 3,749 local governments in the U.S., including 2,899 localities of more than 10,000 in population and 850 counties with either the council-manager or the council-elected executive form of government. Over half of the local governments responded, including 50.7 percent of localities and 48.2 percent of counties. Findings pertaining to the electronic delivery of community services, the digital divide, and e-procurement are discussed.